2021
DOI: 10.1111/hepr.13593
|View full text |Cite
|
Sign up to set email alerts
|

The association of histological progression with biochemical response to ursodeoxycholic acid in primary biliary cholangitis

Abstract: Primary biliary cholangitis (PBC) is currently diagnosed at an early stage; therefore, the number of patients with PBC without symptoms at the time of diagnosis is increasing. However, up to 30% of patients with PBC exhibit the suboptimal response to ursodeoxycholic acid (UDCA) and are at high risk of end-stage liver disease. Obeticholic acid is an approved second-line therapy for patients with PBC that are refractory to UDCA. Novel surrogate endpoints are required to identify individuals eligible for second-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…The Ishak system is based entirely on the extent of fibrosis and provides prognostic information in PBC, a condition characterized by the presence of typical histological features such as non-suppurative destructive cholangitis and ductopenia in its early stages. These data reinforce the fact that ELF score reflects liver fibrosis progression associated with bile duct damage [3] …”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The Ishak system is based entirely on the extent of fibrosis and provides prognostic information in PBC, a condition characterized by the presence of typical histological features such as non-suppurative destructive cholangitis and ductopenia in its early stages. These data reinforce the fact that ELF score reflects liver fibrosis progression associated with bile duct damage [3] …”
Section: Discussionsupporting
confidence: 85%
“…These data reinforce the fact that ELF score reflects liver fibrosis progression associated with bile duct damage. [3] The ELF score of ≥10.0 was highly significantly associated with significant fibrosis in PBC and reliably identifies those highly at risk of experiencing these complications and death. The 2016 United Kingdom's National Institute for Health and Care Excellence (NICE) guidelines have shown that ELF of ≥10.51 could successfully diagnose advanced fibrosis in nonalcoholic fatty liver disease.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Data were collected at baseline and upon treatment with UDCA at a daily dose of 13–15 mg/kg of body weight. The complications of PBC include pruritus, jaundice, ascites, esophageal varices, and hepatocellular carcinoma [ 16 , 17 ]. In this study, patients with PBC were treated with UDCA at a daily dose of 13–15 mg/kg at baseline.…”
Section: Methodsmentioning
confidence: 99%